The social basis of 'evil' in pre-colonial Zimbabwe with particular reference to the practice of killing twins among the Karanga - Mazarire, Gerald C. (Arrupe College, 2016)
Most pre-colonial African societies constructed attitudes and ways of responding to phenomena regarded as "abnormal". Such attitudes were strongly embedded in these societies' perception of life, which was understood to begin at birth. In principle, most societies put to death children born outside the "norm" or those who adopted abnormalities as they grew in order to exorcise themselves from the "curse" these children represented. This was true of breech deliveries, deformed babies, albinos, those who developed their upper incisors before the lower ones, twins and other multiple births.